2011
DOI: 10.1016/j.drugalcdep.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cue reactivity and fronto-striatal functional connectivity in cocaine use disorders

Abstract: Chronic cocaine use is associated with enhanced cue reactivity to drug stimuli. However, it may also alter functional connectivity (fcMRI) in regions involved in processing drug stimuli. Our aims were to evaluate the neural regions involved in subjective craving and how fcMRI may be altered in chronic cocaine users. Fourteen patients with a confirmed diagnosis of cocaine abuse or dependence (CCA) and 16 gender, age, and education-matched healthy controls (HC) completed a cue reactivity task and a resting state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
138
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(155 citation statements)
references
References 67 publications
14
138
1
1
Order By: Relevance
“…In cocaine users, it may have indicated reward/motivational processing related to their chronic cocaine use, whereas in controls it may have indicated their effort to learn and retrieve any information relating to the novel cocaine stimuli (Cohn et al, 2010). Our finding of the causal influence of orbital frontal cortex on ventral striatum extends the study by Wilcox et al (2011), which showed an increased restingstate functional connectivity between orbital frontal cortex and ventral striatum in cocaine users compared with controls.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In cocaine users, it may have indicated reward/motivational processing related to their chronic cocaine use, whereas in controls it may have indicated their effort to learn and retrieve any information relating to the novel cocaine stimuli (Cohn et al, 2010). Our finding of the causal influence of orbital frontal cortex on ventral striatum extends the study by Wilcox et al (2011), which showed an increased restingstate functional connectivity between orbital frontal cortex and ventral striatum in cocaine users compared with controls.…”
Section: Discussionsupporting
confidence: 67%
“…Also, Wilcox et al (2011) showed an increased restingstate functional connectivity between drug-cue processing regions such as orbital frontal cortex and ventral striatum in cocaine users. Based on these studies, we hypothesized that the cocaine users compared with controls would show a different causal interaction pattern among the ROIs of the drug-cue processing network during cocaine-cue exposure.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Chronic use of cocaine, opioids or heroin leads to a decrease in the linkage between the amygdala and VMPFC [46,47,48]. On the other hand, the results of several fMRI studies indicate that resting-state overconnectivity between the NAc and VMPFC occurs in pathological gamblers and chronic users of cocaine or heroin [49,50,51]. Moreover, it has been reported that hypoactivity of the NAc-VMPFC pathway is induced by a cocaine cue in chronic cocaine users [50].…”
Section: Decision Making Systemmentioning
confidence: 99%